Process Simulation of Oxy-Fuel Combustion for A 120 MW Coal-Fired Power Plant Using Aspen Plus - A.O, Odeh; L.A, Okpaire; E.A, Oyedoh (International Journal of Natural Sciences Research, 2021)
Oxy-fuel Combustion is a technology with the potential of drastically reducing the amount of CO2 emission, it relies on the use of oxygen and recycled CO2 instead of air as the oxidant. This helps to reduce the amount of the CO2 and NOx emissions. This study focuses on the components of flue gas produced and their amounts for oxy-fuel combustion in a coal-fired power plant (CFPP) and also the boiler efficiency using the direct (input-output) method. The combustion process of pulverized coal in a 120MW power plant is studied using Aspen Plus 11. The amount of each component in flue gas in coal-fired processes with air or O2/ CO2 (using recycle of 20%, 40%, 60% and 80% of CO2) as oxidizer was obtained. From the process simulation, as the recycle % of CO2 was increased, the flame temperature, CO and NOx emissions were reduced. The simulation results of air combustion were compared with that of oxy-fuel combustion with 80% recycle and it was seen that the flame temperature dropped from 1894oC when air was used as oxidizer to 1679oC for oxy-fuel combustion with 80% recycle. Also, there was a reduction in the amount of NOx produced, but the SOx levels were constant for both combustion processes. The Gross Calorific Value (GCV) of the coal was calculated from its Proximate Analysis using Dulong’s formula and it was used to estimate the Boiler Efficiency using the Direct (Input-Output) method and a value of 83.6% was obtained.